2009
DOI: 10.1556/avet.57.2009.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in some blood coagulation parameters in naturally occurring cases of canine babesiosis

Abstract: Changes in coagulation parameters were studied in dogs naturally infected with Babesia canis canis (n = 30), and haemostasis was evaluated and compared to values obtained from healthy dogs (n = 29). To date, there have not been any studies examining the dynamics of thrombin-antithrombin complex formation in cases of canine babesiosis. Coagulation parameters evaluated before (day 0) and on days 1, 2, and 3 after treatment with imidocarb (6 mg/kg inj. s.c.) included the determination of platelet counts, the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
(46 reference statements)
0
13
0
1
Order By: Relevance
“…Previous studies on B. canis have shown that marked thrombocytopenia was the most common hemostatic change, however very few cases show any gross clinical signs of primary hemostatic abnormalities (Rafaj et al, 2005;Rafaj et al, 2009;Ruiz et al, 2007;Schetters et al, 2009). A similar severe thrombocytopenia is seen in B. rossi with platelet counts reported as low as 14×10 9 /L being a common finding without any associated clinical signs of hemorrhage (Kettner et al, 2003).…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies on B. canis have shown that marked thrombocytopenia was the most common hemostatic change, however very few cases show any gross clinical signs of primary hemostatic abnormalities (Rafaj et al, 2005;Rafaj et al, 2009;Ruiz et al, 2007;Schetters et al, 2009). A similar severe thrombocytopenia is seen in B. rossi with platelet counts reported as low as 14×10 9 /L being a common finding without any associated clinical signs of hemorrhage (Kettner et al, 2003).…”
Section: Discussionmentioning
confidence: 84%
“…It is a circulating glycoprotein that can inhibit thrombin directly and via a number of upstream factors. The AT III levels were significantly decreased in dogs with babesiosis (spot 432) indicating an imbalance in haemostasis defined by the overproduction of thrombin and fibrin [41]. This could be a consequence of inhibitor breakdown and/or liver dysfunction affecting inhibitor production in dogs with babesiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Canine babesiosis was considered the most probable diagnosis, as it can also cause secondary haemostatic disorders (Rafaj et al . , Goddard et al . ).…”
Section: Resultsmentioning
confidence: 99%